Evaluation of equivalency in two recordings of monosyllabic words. - Skinner MW; Holden LK; Fourakis MS; Hawks JW; Holden T; Arcaroli J; Hyde M (Journal of the American Academy of Audiology, 2006)
Thirty 'new' lists of monosyllabic words were created at the University of Melbourne and recorded by Australian and American English speakers. These new lists and the ten original CNC lists (Peterson and Lehiste, 1962) were used during the feasibility study of the Nucleus Research Platform 8 Cochlear Implant System (Holden et al, 2004). Performance was similar across original and new lists for six implanted Australian subjects; for four implanted U.S. subjects, mean performance was 23 percentage points lower with the new than with the original lists. To evaluate differences between original and new lists for the American English recording, 22 CI recipients were administered all 40 CNC lists (30 new and 10 original lists). The overall mean word score for the new lists was significantly lower (22.3 percentage points) than for the original lists. Acoustic analysis revealed that decreased performance was most likely due to reduced amplitudes of certain initial and final consonants. The new CNC lists can be used as more difficult test material for clinical research.